A psicologia e o (des)compromisso social com o SUS - Silva, Emylio César Santos da (2019)
This dissertation aims to investigate through four studies, the training and praxis of psychologists in the context of the Brazilian Public Health System (BPHS/SUS), specifically the Primary Health Care. The first study aims to explore the scientific production of Psychology in the field of Primary Health Care of (BPHS/SUS) between the years 2000 to 2016. A search of national studies in the electronic databases and a systematic review of 255 articles and 22 analyzed in depth. In general, we note the great increase in the academic production in the area and very low articulation between authors of different institutions and no interregional nor international partnership. The second study aims to analyze the intellectual production of the professors of the top Graduate Programs in Psychology in Brazil and its relation with the Brazilian social context. The corpus of the research was formed by 906 articles published by the 54 professors of the 3 Postgraduate Programs with concept 7 in the last quadrennium (2013-2016). Differently from the previous study, it showed a production unrelated to the Brazilian social context and an internationalized production, much of it in the English language (n = 418; 39%) and with paid access. The third and fourth studies are the result of an empirical research whose objectives are to characterize and discuss the professional practices of the psychologists who work in Primary Health Care in the states of Ceara and São Paulo